Credit risk determinants in Sub-Saharan banking systems: Evidence from five countries and lessons learnt from Central East and South East European countries - Eftychia Nikolaidou; Sofoklis Vogiazas (Review of Development Finance, 2017)
Banking systems in Sub-Saharan Africa (SSA) have grown notably over the past decades due to benign macroeconomic, regulatory and financial trends. Nonetheless, downside risks remain elevated by structural issues, commodity price fluctuations, reversal of capital flows and spill-over effects from external shocks in a manner similar to the Central East and South East European (CESEE) countries. In the light of the 2008-2009 Global Financial Crisis, great attention has been given to understanding the causes of banking instability with most of the research focusing on advanced economies and, to a lesser extent, large emerging markets while little attention has been paid to the bank-based financial sectors of Sub-Saharan Africa. Furthermore, there is scarcity of studies aiming at knowledge-sharing among different emerging economies. This paper aims to identify the determinants of bank credit risk by focusing on five SSA countries: Kenya, Namibia, South Africa, Zambia and Uganda. Using the ARDL approach to cointegration, findings indicate that increased money supply conditions have a decreasing effect on NPLs in all counties, banking industry-specific variables play a significant role in the case of South Africa and Uganda while NPLs are driven by country-specific variables in the case of Kenya, South Africa and Zambia. The effect of the Global Financial Crisis is evidenced indirectly. Drawing on evidence from CESEE countries with long experience in banking crises, reforms and financial deepening process, the paper provides lessons for SSA countries and offers policy recommendations in the direction of strengthening banks' balance sheets to ensure financial stability.
Keywords: 650; Non-performing loans; Sub-Saharan Africa; ARDL; Central East and South East European countries